W. V. Quine and Ludwig Wittgenstein: Two approaches to philosophy. - Sigouin, Tara-Lynne. (University of Ottawa (Canada), 2000)
This dissertation explores the works of W. V. Quine and Ludwig Wittgenstein. It provides a detailed and comprehensive discussion of their distinct conceptions of philosophy. It shows how Quine is involved in a scientific philosophy aimed at the discovery of truth and explanation. It also demonstrates how Wittgenstein's critical approach attempts to dissolve philosophical problems and theories. The main purpose of this work is to explain how a proper understanding of each philosopher's framework of study, is crucial to the understanding and criticism of their respective philosophical ideas. The only way to properly refute Quine's theories is to evaluate them in a scientific framework. Any other interpretation could change his intention and weaken his arguments. Similarly, the only way to refute Wittgenstein's claims is to interpret them in everyday language. However, this is not to say that either view can be refuted. It is simply to point out that any attempt to oppose Wittgenstein's claims from a scientific viewpoint, or Quine's from a non-scientific perspective, will be flawed since it is contrary to the way in which each view was conceived.
Keywords: Philosophy.